Моделі та методи безпечної маршрутизації в IoT - Егбе Годсон Агбара (My University, 2020)
The object of research is a process of secure routing in the IoT networks. The subject of research is the models, methods, and protocols of secure routing in IoT networks. The purpose of the work is the analysis of models, methods, and protocols of secure routing in IoT in order to increase network security. Research methods are analytical modeling, simulation, formalization, and comparison.
Models and Methods of Secure Routing in IoT
Keywords: secure routing; iot; trust based protocols; modeling